2021
DOI: 10.1088/1755-1315/803/1/012047
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of carrageenan and xanthan gum in “raja” banana (Musa sapientum) for coating application

Abstract: “Raja” banana (Musa sapientum) is a type of banana that is often consumed in Indonesia. Raja bananas provides several benefits due to nutrients content, such as bioactive phenolics, antioxidants, potassium, vitamin C and also high carbohydrate content that changes color and texture during ripening. Preservation method was used to suppress this physical changes. This research was done to analyze color in “Raja” bananas and its shelf life after the treatment using iota carrageenan and xanthan gum as coating mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Many researchers have IOP Publishing doi:10.1088/1755-1315/1155/1/012014 2 studied polysaccharide-based coatings, including polysaccharide from banana cellulose [2], cactus [3], and soybean [4], various kinds of seeds [5], tapioca [6], jicama [7], sago starch [8]. The edible coating could maintains the quality of commodities such as on banana [9], strawberry [10]. Moreover, previous study reported that starch-based coating is also contribute on reducing oil content of fried potato chips [11].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have IOP Publishing doi:10.1088/1755-1315/1155/1/012014 2 studied polysaccharide-based coatings, including polysaccharide from banana cellulose [2], cactus [3], and soybean [4], various kinds of seeds [5], tapioca [6], jicama [7], sago starch [8]. The edible coating could maintains the quality of commodities such as on banana [9], strawberry [10]. Moreover, previous study reported that starch-based coating is also contribute on reducing oil content of fried potato chips [11].…”
Section: Introductionmentioning
confidence: 99%